2007
DOI: 10.1007/s11936-007-0018-1
|View full text |Cite
|
Sign up to set email alerts
|

The clinical assessment of retinal microvascular structure and therapeutic implications

Abstract: Examination of the retinal microvasculature is widely used to assess diabetic eye disease and as an indicator of target organ damage in hypertension. The diagnostic value of grading of hypertensive retinopathy is dubious; however, many recent studies have demonstrated that hypertensive retinopathy is associated with a range of risk factors for cardiovascular disease and may predict cardiovascular events independently of blood pressure. Developments in digital imaging and computer-assisted analysis have facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…6 -8 While these abnormalities are reflective of large artery disease, there is also evidence of disturbance in small arteries and arterioles, down to the level of the peripheral vascular beds (i.e., the microcirculation), 9,10 an example of which is retinal disease, as is often present in diabetic and hypertensive retinopathy. 11,12 However, it is as yet unclear whether microcirculatory changes are contributors to, or sequelae of, the disease process.…”
Section: Purposementioning
confidence: 99%
“…6 -8 While these abnormalities are reflective of large artery disease, there is also evidence of disturbance in small arteries and arterioles, down to the level of the peripheral vascular beds (i.e., the microcirculation), 9,10 an example of which is retinal disease, as is often present in diabetic and hypertensive retinopathy. 11,12 However, it is as yet unclear whether microcirculatory changes are contributors to, or sequelae of, the disease process.…”
Section: Purposementioning
confidence: 99%
“…In hypertension, both arteriolar narrowing [7][8][9][10] and rarefaction [9,10] are evident in the retina using quantitative assessment of retinal photographs acquired by noninvasive techniques. Retinal microvascular abnormalities have been reported to predict cardiovascular disease [11][12][13], coronary heart disease [12,14,15], stroke [16], incident hypertension [17] and new onset type 2 diabetes [18]; in consequence, there is increased interest in quantitative retinal assessment as a clinical tool [19].…”
Section: Introductionmentioning
confidence: 99%
“…Regression of retinal microvascular abnormalities may be of particular relevance to stroke, as microvascular disease is an important cause of stroke and the retinal circulation is part of the cerebral circulation [19].…”
Section: Introductionmentioning
confidence: 99%
“…The retinal circulation is closely related to the cerebral circulation and offers a rare opportunity to visualize the arteriolar and venular circulations in man in vivo using noninvasive techniques. Examination of the retinal fundus is commonly used to assess retinal microvascular damage in diabetes and as an indicator of target organ damage in hypertension 9 . Recent studies have shown that the existence of retinopathy and, especially, more quantitative measures of retinal microvascular abnormalities, even in those without diabetes and hypertension, predict incident cardiovascular disease (CVD), including stroke 29 26 18 and ischemic heart disease, 24 , heart failure 32 , hypertension 33 , as well as type 2 diabetes, 34 , often independently of other traditionally used risk factors.…”
mentioning
confidence: 99%